Natural Phytochemicals in Bladder Cancer Prevention and Therapy - Xia, Yong; Chen, Ruijiao; Lu, Guangzhen; Li, Changlin; Lian, Sen; Kang, Taek-Won; Jung, Young Do (Frontiers in Oncology, 2021)
Phytochemicals are natural small-molecule compounds derived from plants that have attracted attention for their anticancer activities. Some phytochemicals have been developed as first-line anticancer drugs, such as paclitaxel and vincristine. In addition, several phytochemicals show good tumor suppression functions in various cancer types. Bladder cancer is a malignant tumor of the urinary system. To date, few specific phytochemicals have been used for bladder cancer therapy, although many have been studied in bladder cancer cells and mouse models. Therefore, it is important to collate and summarize the available information on the role of phytochemicals in the prevention and treatment of bladder cancer. In this review, we summarize the effects of several phytochemicals including flavonoids, steroids, nitrogen compounds, and aromatic substances with anticancer properties and classify the mechanism of action of phytochemicals in bladder cancer. This review will contribute to facilitating the development of new anticancer drugs and strategies for the treatment of bladder cancer using phytochemicals.